Biochar-embedding iron-alginate microspheres derived from bagasse by one-step microwave pyrolysis/activation for enhanced Cr(VI) removal - Wang, Hongfei; Zhao, Xiqiang; Yang, Xinfei; Sun, Shuang; Wang, Wenlong; Mao, Yanpeng; Song, Zhanlong (Frontiers in Energy Research, 2022)
In this paper, two types of adsorption materials SA-C-Fe and SA-C-Fe(C) were prepared using bagasse biochar produced by one-step microwave pyrolysis and activation for Cr(VI) removal of wastewater. The adsorption materials were characterized, and Cr(VI) adsorption performance, kinetics and thermodynamics on adsorption materials were studied. Results display that microwave/activation contributes to developed pore structure and abundant active functional groups, resulting in high Cr(VI) adsorption capacities. The optimal preparation conditions for biochar is: microwave power 500 W, ZnCl2/bagasse ratio 2.5:1 and pyrolysis/activation time 15 min, and the specific surface area of biochar is 1787.64 m2/g. The Cr(VI) adsorption of the two materials is more in line with the pseudo-second-order kinetic model, and the adsorption process is dominated by chemical adsorption. The static removal experiment of Cr(VI) using SA-C-Fe and SA-C-Fe(C) has the best removal effect at pH=2, and the whole adsorption process is more in line with the Langmuir-Freundlich isotherm model. Calculated by the pseudo-two-order kinetic model and the Langmuir-Freundlich isothermal model, the maximum adsorption rate for Cr(VI) of SA-C-Fe and SA-C-Fe(C) are 211.87 mg/g and 388.92 mg/g, respectively. The removal process is mainly dominated by three mechanisms: electrostatic adsorption, ion exchange and redox reactions. The improvement of Cr(VI) adsorption capacity is attributed to more developed pore structure. The results offer beneficial reference for the application of low-cost carbon-based adsorption materials for pollutants separation, and effectively realize the utilization of bagasse pyrolysis by-products.